PENERAPAN METODE LATIHAN BERSTRUKTUR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BILANGAN BERPANGKAT DI KELAS X MIA 5 SMA NEGERI 4 PALU - Mayanti, Desi; Muh. Hasbi, Muh. Hasbi; Paloloang, Baharuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The aim of of this research was to describe the application of structured training methods that can improve student study result in the material exponential number in class X MIA 5 SMA Negeri 4 Palu. This research is aclassroom action research (CAR). As the research design refers to the design of the research of Kemmis and Mc. Taggart that is (1) planning, (2) action, (3) observation and (4) reflection. This research was conducted in two cycles. The data collected in this research is activity of teachers in managing learning, activity of students in the following learning, the results of the initial test and final test results of action. The results showed that the application of structured training methods that can improve student study result in the material exponential number, through the steps that (1) preparing for learning, (2) the presentation of the implementation, (3) test behavior and (4) follow-up.